1999
DOI: 10.1530/eje.0.1410644
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Reg and cytokeratin 20 during ductal cell differentiation and proliferation in a mouse model of autoimmune diabetes

Abstract: Objective: To evaluate the existence of beta-cell differentiation and proliferation in the low-dose streptozotocin (ld-STZ) mouse model of autoimmune diabetes. Design: We studied the expression of Reg protein and cytokeratin 20 (CK20), the presence of proliferative phenomena (judged by the incorporation of bromodeoxyuridine (BrdU)), and the co-expression of Reg, CK20 or BrdU with insulin. Materials and methods: Diabetes was induced in male C57Bl6/J mice by administration of ld-STZ. The animals were killed at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…A recent study by Sanchez et al (37), investigating the expression of RegI and -II in the NOD mouse by using RegII peptide-specific antibodies, could find neither RegI nor -II in the endocrine pancreas, but showed localization of Reg in the acinar cells of the exocrine pancreas. However, colocalization of Reg with insulin-staining and localization in ductal epithelial cells have been reported by Anastasi et al (21) in a model of streptozotocin-induced diabetes in C57BL/6J mice. This latter finding is in agreement with our observations of Reg expression in the pancreas of the NOD mouse.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A recent study by Sanchez et al (37), investigating the expression of RegI and -II in the NOD mouse by using RegII peptide-specific antibodies, could find neither RegI nor -II in the endocrine pancreas, but showed localization of Reg in the acinar cells of the exocrine pancreas. However, colocalization of Reg with insulin-staining and localization in ductal epithelial cells have been reported by Anastasi et al (21) in a model of streptozotocin-induced diabetes in C57BL/6J mice. This latter finding is in agreement with our observations of Reg expression in the pancreas of the NOD mouse.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, all murine Reg genes and the gene for HIP/PAP carry one or more interleukin-6 (IL-6) response elements in their 5Ј flanking region (17,20). Recent immunohistological data in streptozocin-treated C57BL/6J diabetic mice demonstrate that Reg is colocalized with insulin in the islets and that in the remainder of the pancreas, Reg expression is restricted to the ductal epithelia (21). Reg has also been colocalized immunohistochemically with insulin in the ␤-cell secretory granules of regenerating rat ␤-cells, and immunoreactive HIP/PAP has also been detected in human islets (22,23).…”
mentioning
confidence: 99%
“…(3) When DNA is massively damaged, PARP is rapidly activated to repair the DNA (1, 9 -13), and the complex for Reg gene transcription is not formed at all. remission phase of diabetes (37), in islets of nonobese diabetic mice during active diabetogenesis (38) and pancreatic ductal cells, which are thought to be progenitor cells of ␤ cells, during differentiation and proliferation in a mouse model of autoimmune diabetes (39), and inflammation in and͞or around islets was involved in these cases. The findings in this paper showed that the combined addition of typical inflammatory mediators (IL-6 and the glucocorticoid analogue dexamethasone) induced Reg gene expression and that PARP inhibitors such as nicotinamide and 3-aminobenzamide enhanced the induction.…”
Section: Discussionmentioning
confidence: 99%
“…Such an ability of HGF to promote beta-cell terminal differentiation extends the spectrum of activities of this growth factor, previously shown to induce in vivo and in vitro differentiation of beta cells (Otonkoski et al 1994a,b, 1996, García-Ocaña et al 2000, Gahr et al 2002. HGF has also been shown to increase in vitro the expression of Reg, a protein implicated in pancreatic regeneration (Anastasi et al 1999, Kobayashi et al 2000, and to convert, when administered alone or in combination with activin A, pancreatic acinar AR42J cells into insulin-producing cells (Mashima et al 1996). Additionally, the capacity of HGF to induce the differentiation of a ductal cell line (ARIP) into insulin-producing cells suggests that this growth factor may be able to recapitulate, at least in part, the neogenetic process that leads from the cell expansion of precursor cells to the terminal differentiation of insulin-producing cells.…”
Section: Discussionmentioning
confidence: 71%